Policing technology-facilitated sexual violence against adult victims: police and service sector perspectives - Powell, Anastasia; Henry, Nicola (Policing & society, 2018)
To date, the majority of attention to technology-facilitated sexual violence (TFSV) in both policy and practice has been on child sexual exploitation and abuse. Far less attention has been paid to digital sexualised violence against adult members of the population. The aim of this paper is to examine police responses to these serious and emerging harms, which we identify as including the following: (1) online sexual harassment; (2) gender and sexuality-based harassment; (3) cyberstalking; (4) image-based sexual exploitation (including 'revenge pornography'); and (5) the use of communications technologies to coerce a victim into an unwanted sexual act. While these are variously criminal offences, unlawful civil behaviours or not subject to criminal or civil sanctions or remedies, we claim in this paper that they exist on a continuum of violence and yet the 'real' harms of TFSV are frequently minimised in practice. Drawing on 30 stakeholder interviews with police, legal services and domestic and sexual violence service sector providers, we explore the issues, challenges and promises of law enforcement in this area. We argue that greater attention must be paid to recognising the serious harms of digital abuse and harassment; the role of criminal law in responding to these behaviours; and the importance of investing in police resources to adequately tackle these growing behaviours in a constantly shifting and amorphous digital era.